Difference in response of water use to evaporative demand for codominant diffuse‐porous versus ring‐porous tree species under N addition in a temperate forest. Issue 4 (8th February 2017) - Ouyang, Lei; Zhao, Ping; Zhu, Liwei; Zhang, Zhenzhen; Zhao, Xiuhua; Ni, Guangyan
Abstract: In this study, we explored the impacts of nitrogen (N) addition on water transpiration of codominant trees with different wood anatomy and their response of water use to varying vapor pressure deficit (VPD). Three tree species, diffuse‐porous Liquidambar formosana Hance (maple), ring‐porous Quercus variabilis Blume (cork oak), and Quercus acutissima Carruth (sawtooth oak), were selected for this research. These temperate forest trees grow in a climatic transitional zone located in Henan Province of Central China, and have been under N addition treatments of different levels since April 2013. The N treatments include control, low N (25 kg N ha −1  year −1 ), and high N levels (50 kg N ha −1  year −1 ). The measured data of stem sap flow from April to October 2015 showed that maple trees used more water than oak trees and N addition generally decreased the water transport of maple and sawtooth oak but induced no significant change of water transpiration for cork oak. Water use in maple increased with VPD, whereas relatively flat response for both oaks was observed, suggesting a much stricter stomatal control. Under N addition, water transport in all tree species showed a significant decline in the wet period (August), during which there were more precipitation and cloudy days than in dry May when VPD is >1.80 kPa. However, changes of vessel size, hydraulic conductivity, and root biomass that are associated with N addition for both ring‐ and diffuse‐porous species remain unknown and require further investigation.